Finance in Africa Achievements and Challenges - Beck, Thorsten 1967- (The World Bank, 2009)
In spite of shallow financial markets, Sub-Saharan Africa will not escape the repercussions of the global financial crisis. The global turmoil threatens the progress Sub-Saharan Africa has made in financial sector deepening and broadening over the recent years and underlines the importance of continuing and deepening the necessary institutional reforms. In this context it is important to define the role of government in expanding financial sectors in a sustainable and market-friendly manner. Foreign banks have brought more benefits than risks for their host economies in Sub-Saharan Africa, but are certainly not a panacea and not a substitute for institutional and policy reform. The profile of foreign banks, however, has changed, with more and more regional banks emerging. This trend toward regional integration is promising as it might allow the small African financial system to reap benefits from scale economies, but it also requires regulatory and supervisory improvements and coordination across the region